Lie Symmetry Analysis and Exact Solutions of the Time Fractional Gas Dynamics Equation - Hashemi, M. S.; Baleanu, Dumitru; Baleanu, D. (Natl inst Optoelectronics, 2016)
Finding the symmetries of a given fractional differential equation is a hot topic in the field of fractional differentiation and its applications. In this manuscript, the Lie symmetries of the time fractional gas dynamics (TFGD) equation are analyzed and new exact solutions are obtained.
Lie symmetry analysis and exact solutions of the time fractional gas dynamics equation
Hashemi, Mir Sajjad/0000-0002-5529-3125
Keywords: Fractional Gas Dynamics Equation; Lie Symmetry Method; Erdelyi-Kober Fractional Differential Operator